Contexts, questions, and answers: What is new in youth and adult education? - Sales, Sandra Regina; Paiva, Jane (Education Policy Analysis Archives, 2013)
This article discusses a set of provocative questions emerging from the articles received for this special issue on youth and adult education, and how researchers have been answering them. These are reflections on the meaning of learning of youth and adults in the face of the complexity of contemporary demands, which transformed traditional meanings of learning as well as the ways a diversity of young and adult subjects learn in social practices, including the condition of workers in permanent formation. The analysis shows experiences of diverse time-spaces, identities, languages, and ways of seeing reality towards the constitution and attribution of senses and understandings of a world. In these diverse experiences contacts are interweaved, nets are formed, ideas are spread and bonds are created in the dialogue among researchers working in the field of youth and adult education in three continents.